2015
DOI: 10.4018/ijesma.2015010102
|View full text |Cite
|
Sign up to set email alerts
|

E-Government Service Research Development

Abstract: Electronic service in the domain of e-Government has been gaining research attention over past two decades. This paper reports on a literature review of the published e-Government service research and provides an analysis of the research development in terms of research themes, regional context, research perspective, data analysis method, and research approach. The results of this analysis can serve the e-Government research communities as a means of understanding the e-Government service research development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 183 publications
0
6
0
Order By: Relevance
“…Financial reports are used to compare the realization of income, expenditure, transfers and financing with a predetermined budget, assess financial conditions, evaluate the effectiveness and efficiency of a reporting entity, and help determine its compliance with statutory regulations. The reporting entity is obliged to report the efforts that have been made and the results achieved in carrying out activities in a systematic and structured manner in a reporting period for the purposes of (Pumphrey et al 2008, Hasan et al, 2019.…”
Section: The Role Of Financial Reportsmentioning
confidence: 99%
“…Financial reports are used to compare the realization of income, expenditure, transfers and financing with a predetermined budget, assess financial conditions, evaluate the effectiveness and efficiency of a reporting entity, and help determine its compliance with statutory regulations. The reporting entity is obliged to report the efforts that have been made and the results achieved in carrying out activities in a systematic and structured manner in a reporting period for the purposes of (Pumphrey et al 2008, Hasan et al, 2019.…”
Section: The Role Of Financial Reportsmentioning
confidence: 99%
“…The results of the study have shown that the evaluation conducted in a government institution allows analyzing and critically evaluating the process at a particular level in the government institution (Butt, 2014). Hasan (2015) has made a literature analysis of studies conducted in the e-government sphere. The analysis of the studies are conducted with the intent of research improvement by taking into account the regional context, the perspective of studies, the method of data analysis, and the analysis of research approaches.…”
Section: International Practice On E-service Evaluationmentioning
confidence: 99%
“…The results obtained in the study cover the research works related to e-government services, service development, evaluation, and mutual communication. The research works considered the topic from the point of view of advanced and developing countries, and empirical data analysis methods were used (Hasan, 2015). Taherdoost, et al (2015) summarized e-services and explored the conceptual perspectives comprehensively.…”
Section: International Practice On E-service Evaluationmentioning
confidence: 99%
“…A considerable number of research efforts on interoperability are conducted both in industry and academia. The interoperability process is similar to the process used while composing services in Service Based Application (SBA) [21]. Many initiatives for modeling SBAs have been proposed, namely languages (e.g., BPEL4WS, OWL-S, Petri nets, etc.)…”
Section: Approach Overviewmentioning
confidence: 99%